Daptomycin Produces an Enhanced Bactericidal Activity Compared to Ceftriaxone, Measured by [(3)H]Choline Release in the Cerebrospinal Fluid, in Experimental Meningitis Due to a Penicillin-Resistant Pneumococcal Strain without Lysing Its Cell Wall - Stucki, A. (American Society for Microbiology, 2007)
Daptomycin monotherapy was superior to ceftriaxone monotherapy and was highly efficacious in experimental pneumococcal meningitis, sterilizing the cerebrospinal fluid (CSF) of three of three rabbits after 4 to 6 h. With daptomycin therapy only a negligible release of [(3)H]choline as marker of cell wall lysis was detectable in the CSF, peaking around 250 cpm/min after 4 h, compared to a peak of around 2,400 cpm/min after 4 to 6 h for the ceftriaxone-treated rabbits.